Aplikasi POS Berbasis Web Terintegrasi Dengan Whatsapp Pada Fuku Petshop - Hanggaraxsha, Irwan; Gunawan, Dedi (The Indonesian Journal of Computer Science, 2024)
The Point Of Sale (POS) application is a service created to simplify the business activity process for entrepreneurs. Every transaction, whether sales or purchases, is important to record to ensure the accuracy of transaction reports. However, at Fuku Petshop, the recording method still uses conventional transaction books, which are prone to data loss and inaccuracies. Fuku Petshop, a shop located in Madiun, felt the need to adopt a computerized POS system to monitor sales, purchase and stock transactions more efficiently. Apart from that, integration with the WhatsApp application is also part of the goal of this system. In developing the POS system, utilizing the PHP programming language and MySQL database, using the CodeIgniter framework. The development approach adopted is the waterfall method. To ensure the quality of the system being developed, testing is carried out using black box techniques and also using the System Usability Scale (SUS) method. The results of testing using the black box technique state that the POS application at Fuku Petshop runs well and for SUS testing the average value is 81, which indicates Excellent qualifications and is included in the Acceptable classification, indicating the system is ready for use.